Grounding AI - Ficozzi, Matilde; Rodighiero, Dario; Jacomy, Mathieu; Munk, Anders Kristian (University of Groningen Press, 2026)
You are seeing a map — but not of streets or cities. This is a map of two million scientific papers about artificial intelligence, machine learning, and algorithms. Each dot is a paper. Each cluster is a conversation happening in science, right now, about how algorithms are being put to work in the world. Like any city map, this one invites you to explore. You can zoom in on a neighborhood, follow a path, or simply wander. The further you walk, the more the landscape changes — from medicine to education, from language to vision, from prediction to control. Take your time with it. Ask yourself which of these applications you had heard of, which ones surprised you, and whether more of them should be part of the public conversation we are all having about AI. Grounding AI is a collaboration between DTU ECHOlab, AAU Tantlab, and the University of Groningen. The foldable map Grounding AI: A Foldable Map of Two Million Research Papers has been published to celebrate the Jantina Tammes School of Digital Society, Technology and AI. Publisher: University of Groningen Press Broerstraat 4 9712 CP Groningen Visualization Design: Mathieu Jacomy Layout Design: Matilde Ficozzi and Dario Rodighiero Typesetting and production support: LINE UP boek en media bv